Imports: Blessing in Disguise to Nepal Government (Nepalese Journal of Management Research, 2024)
Trade has played an influencing factor for the economy to achieve its economic growth. For that, economies are highly engaged on expanding their exports while wanted to minimize imports. However, for developing countries like Nepal, imports have also been an integral part for the collection of government revenue. This article tries to study the relationship between government revenue and imports in context to Nepal following bivariate time series analysis along with some empirical analysis. Data are retrieved from economic survey and macroeconomic indicators from the fiscal year 2001/02 to 2021/22. The result shows huge rate of dependence of government revenue on imports and has became a disguised blessing.